IMPROVING MATHEMATICS LEARNING OUTCOMES USING CONCRETE MEDIA (REAL) KPK AND FPB MATERIALS ON STUDENTS OF CLASS VI SD STATE 001 KEPENUHAN DISTRICT OF KEPENUHAN DISTRICT ROKAN HULU - Eka Yulia Mesra (Indonesian Journal of Basic Education, 2021)
This study is to improve the learning process in terms of teacher and student activities so as to find out whether there is an increase in student mathematics learning outcomes after implementing the application of learning using concrete (real) media in class VI students of SD Negeri 001 Kepenuhan District Kepenuhan, Rokan Hulu Regency totaling 31 students. This research is a Classroom Action Research (CAR) which consists of two cycles. Data collection techniques in this study were carried out by observation techniques (field notes, observations, interviews, photos) and performance tests. The results showed that there was an increase in the mathematics learning outcomes of sixth grade students at SD Negeri 001 Kepenuhan District Kepenuhan Rokan Hulu Regency. This can be seen in student learning outcomes in the test in the first cycle and the daily test in the second cycle, where the average value of student learning outcomes in the pre-cycle is 55.81, in the first daily test the average value of student learning outcomes is 64.84 and on the second daily test the average value of student learning outcomes is 77.74.